PENGARUH METODE LATIHAN DISTRIBUTED PRACTICE DAN MASSED PRACTICE TERHADAP KETERAMPILAN PUKULAN BACKHAND SMASH PADA PERMAINAN TENIS MEJA - Muhammad Kamal (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
This study aims to determine the difference in the effect of distributed practice and massed practice methods on backhand smash skills in table tennis. This research is experimental research with the type of Quasi Experimental research. The design used in this study was a two-group pretest-posttest design. The population in this study were athletes from several table tennis clubs with a total number of 40 athletes. The sampling technique used is a total sampling technique, where all members of the population are used as samples. The sample was then divided into 2 groups each consisting of 20 athletes in each group. Data analysis technique with T-test at a significance level of = 0.05. The results of this study indicate that the distributed practice method has a better effect than the massed practice method on the results of the backhand smash skill, where the p value = 0.015 (P <0.05).